2010
DOI: 10.1177/039463201002300208
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Allergenicity of Constituents of Myoga Using the Murine Local Lymph Node Assay

Abstract: Myoga (Zingiber Myoga Roscoe) is a perennial plant with a pungent smell from its flower buds. It is native to East Asia and has been reported to cause allergic contact dermatitis. The purpose of this study is to assess the allergenicity of myoga related to its major chemical components, «-pinene, p-pinene, limonene, llmonene oxide and p-phellandrene, which are supposed to be the causative agents of contact dermatitis among myoga cultivators. We performed a toxicity study of the volatile constituents of myoga … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“… Sensitization class according to LLNA; for SDS classification human data were taken 13 ; for α‐pinene different results were reported 23,24 . …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Sensitization class according to LLNA; for SDS classification human data were taken 13 ; for α‐pinene different results were reported 23,24 . …”
Section: Resultsmentioning
confidence: 99%
“…Patch tests revealed allergic reactions and α‐pinene was confirmed as a weak allergen in the guinea pig maximization test. However, it failed to induce a positive response in the LLNA 23,24,40 . Besides, pinenes do not have the structural properties to bind covalently to skin proteins 39 .…”
Section: Discussionmentioning
confidence: 98%
“…According to the Food and Drug Administration, camphor-containing products cannot exceed 11% camphor. In addition, allergic contact dermatitis has been reported following the use of α-pinene, β-pinene, and myrcene [175,177,178,190]. This issue draws attention on the need to further explore the safe concentrations of terpenes for therapeutic proposes [191].…”
Section: Discussionmentioning
confidence: 99%
“…However, in addition to the beneficial effects of the above volatile terpene compounds on AD, many adverse cases have also been reported. In evaluation studies using various assays, many compounds including α-pinene, β-pinene, limonene, beta-phellandrene, and camphor, have been reported to show positive allergenicity responses causing contact dermatitis [175][176][177]. Despite their beneficial activities as antioxidants, some volatile terpene compounds can autoxidize rapidly to skin allergens on air exposure.…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…Soluble YCAM-I, for example, does not predict the risk of future myocardial infarction in apparently healthy men (41)(42)(43)(44). However, research has repeatedly and unequivocally demonstrated the essential role of YCAM-I in experimental atherosclerotic lesion initiation and progression (45)(46)(47)(48)(49) .…”
Section: Genesis Of Atherosclerosismentioning
confidence: 99%